Synchronous skin and gastrointestinal Kaposi's sarcoma in two patients with HIV/AIDS - adminCarrillo-Ñañez, Leonidas (2019)
t is showed the case of two male patients, 74 year-old heterosexual and 29 year-old homosexual, both carriers of the virus of human immunodeficiency virus (HIV) in stage C3, with Kaposi's sarcoma of skin, oral cavity and extensive involvement of the digestive tract. In the first case, it was found lesions of esophagus, stomach and duodenum; and, in the second case, besides similar lesions in the entire length of the colon were found plus neurocriptococcocis and strongyloidiasis. After treatment, both patients had an adequate evolution.